Isolasi dan Uji Kualitatif Hidrolisat Jamur Penghasil Enzim Selulase dari Tanah Tumpukan Ampas Tebu - Yosmar, Rahmi; Suharti, Netty; Rasyid, Roslinda (Jurnal Farmasi Andalas, 2013)
A Study on the isolation and qualitative test Â of cellulose producer fungus from waste product soil of Saccharum officinarum in Tabek Patah West Sumatera has been done by usingÂ  Czapek Dox Agar (CDA) selective media. The selulolitic ability test of this isolated fungus by giving the congo red solution on the surface of medium that was enriched with Carboxy Methyl Cellulose, the formed of transparent area around the colonies showed that the fungus has the capability to decomposed the cellulose. The hydrolitic enzyme in glucose form was analyed using Fehling solution and Thin Layer Chromatograph. The result from this research showed that the sample consist of two species of decomposed cellulose fungus Aspergillus terreus Thom and Rhizopus sp.